Wholesome Coin: A pHealth Solution to Reduce High Obesity Rates in Gulf Cooperation Council Countries Using Cryptocurrency - Alsalamah, Hessah A.; Nasser, Shorog; Alsalamah, Shada; Almohana, Albatoul I.; Alanazi, Areej; Alrrshaid, Fay (Frontiers in Blockchain, 2021)
Obesity is considered one of the leading causes of chronic and noncommunicable diseases; these include diabetes, cardiovascular disease, and cancer. The obesity prevalence is threefold higher in the Arab Gulf Cooperation Council (GCC) population than the rest of the world and leaves healthcare providers within the region with no alternative than to offer continuous and sustainable healthcare services. Obesity prevention would be more economical for governments than providing treatment. Preventing obesity is challenging because it requires motivating individuals to live a healthy lifestyle. Personal health (pHealth) has recently been actively involved in finding solutions to encourage healthy living. However, pHealth does not address the high percentage of people lacking the desire to maintain healthy living plans, which could have a negative effect on attempts aimed at reducing obesity prevalence. This study sheds light on the challenges faced by the GCC governments in reducing high obesity rates using pHealth; we propose a solution, Wholesome Coin, which incorporates advanced technologies to help governments reduce high obesity rates. Wholesome Coin has two components: one uses wearable IoT (WIoT) to help patients manage their behavior by tracking their physical activities and diet, and the other utilizes blockchain technology to help healthcare payers to incentify patients to maintain a healthy living plan by awarding digital coins that can be redeemed for real goods and services. GCC governments’ adoption of Wholesome Coin could improve the quality of life of obese patients in a seamless, secure, and self-motivated manner, resulting in a healthier tomorrow, especially amid challenging times featuring global social distance campaigns.